MENGENAL AJARAN GERAKAN SYI’AH - Mustolehudin Mustolehudin (Harmoni, 2012)
The term Syiah means followers, today conventionally it refers to a moslem group, after the death of the prophet Muhammad SAW, who belive that position of leaders of moslem people is prerogatively holded by Ali and his descendants. The are believed to be sacred. In basic, the practices of Syiah is not much different from other moslem groups (Sunni). Those some manifested differences are in terms of ritual ablution before prayers (wudlu), praying kneeling position (sujud), praying time, temporary marriage (mut`ah), the way folding hand in praying, optional praying in fasting month and one fith tax (khumus).